KECERNAAN BAHAN KERING DAN BAHAN ORGANIK RANSUM TERNAK KAMBING KACANG YANG DIBERI SUPLEMENTASI DEDAK PADI DAN DAUN TURI - Aholiab Aoetpah; Twen O. Dami-Dato; Stefanus Ghunu (Politeknik Pertanian Negeri Kupang, 2010)
Dry And Organic Matter Digestibility Of Kacang Goats Offered Native Grass Supplemented With Rice Meal And Sesbania Leafs. A study on the effect of rice meal and sesbania leafs supplementation on dry and organic matter digestibility of kacang goats offered native grass has been carried out using 12 male goats (6-9 months old) in a block completely randomized design. The goats were grouped into 4 and then each group was treated as R0 = 100% native grass (control), R1 = 75% native grass + 20% sesbania leafs + 5% rice meal, R2 = 50% native grass + 40% sesbania leafs + 10% rice meal or R3 = 25% native grass + 60% sesbania leafs + 15% rice meal. Replication was 3 times for each treatment so there are 12 experimental units. Data was analyzed by Analysis of variance (ANOVA) and the difference among treatments was further analyzed by Duncan’s multiple range tests. Results showed that there is a strong significant difference (P<0.01) among dry matter digestibility. Further test showed that there is a strong significant difference (P<0.01) between R3 and either R0, R1 or R2. Between R2 and R0 there is only a significant (P<0.05) difference. There is no difference (P>0.05) between R2 and R1 as well as R1 and R0. Organic matter digestibility was significantly (P<0.01) differ among treatments. Further test showed that a strong significant (P<0.01) difference was recorded between R3 and either R0, R1 or R2. Similarly, the difference between R2 and R0 as well as R1 and R0 was recorded. There is no significant difference (P>0.05) between R2 and R1. It can be concluded that dry and organic matter digestibility of kacang goats increases according to the increase of sesbania leafs and rice meal supplementation. It was suggested to use sesbania leafs and rice meal in the ration of fattening goats and also it was suggested a further experiment by using different ration formulation composed of these feedstuffs.Keyword: dry matter, organic matter, kavang goat, rice meal, sesbania leaf